Music, Art and Emotion Depictions of the Night Inspired by Romantic Art Song - Cupido, Conroy (AOSIS, 2022)
This book explores the ways in which four visual artists make sense of referentialism and emotion in music. By listening to five art songs by Schubert, Strauss, Fauré and Berlioz they were inspired to create new artworks as a result of their understanding of the meaning of the art songs. This was done without an understanding of the text, and the artists had to rely on referential meaning in music as well as the perceived or evoked emotions elicited by listening to the art songs. The artworks created as a result of this project were exhibited at the Aardklop National Arts Festival, entitled Nagmusiek. This was a multi-modal exhibition featuring music, art and text. This book employs Artistic Research and Phenomenology in order to understand this phenomenon, as I explored the artists' creative processes, experiences and the tacit knowledge embedded in their artefacts. This book would provide readers access to 20 new artworks, each created as a result of the artists' interpretation of the meaning they ascribed to art song. Their creative process is also examined and synthesised with existing literature on emotion and referentialism in music.